Implementasi Manajemen Risiko Operasional pada Toko Buah Istana Pahlawan Perspektif Ekonomi Islam - Faisal Dhani Pauji; Husna Ni’matul Ulya (Niqosiya: Journal of Economics and Business Research, 2025)
Currently, competition in micro, small, and medium enterprises cannot be separated from the ability of each businessman to manage risks in their business. The Istana Buah Pahlawan Fruit Shop is one of the businesses engaged in the trade sector with various fruit products sold. This shop has operational risks that affect the sustainability of its business. There are various obstacles in its operational activities such as product damage, slow distribution, and market fluctuations or changes that are difficult to predict. These various problems have been managed in such a way as to reduce the losses incurred. However, there is still a decrease in turnover which requires the shop to implement more effective risk management so that stabilization of business activities in the shop can be achieved. The purpose of this study is to analyze the implementation of risk management in the Istana Buah Pahlawan fruit shop business. The type of research used by the researcher is field research using a qualitative approach. The data collection technique used by the researcher is interviews. In its implementation, the Istana Buah Pahlawan fruit shop applies simple risk management without using theory, namely only by relying on experience, estimates, and good relationships with related parties to manage risk.